Identifikasi Mikroalga dari Divisi Chlorophyta di Waduk Sumber Air Jaya Dusun Krebet Kecamatan Bululawang Kabupaten Malang - FAUZIAH, SHADDIQAH MUNAWAROH; LAILY, AINUN NIKMATI (Bioedukasi: Jurnal Pendidikan Biologi, 2015)
Reservoir is a water puddle created by humans by damming up the river and the water is stored with multiple destinations, such as for drinking, such as for drinking water, hydropower, flood control and many more. In addition there are fish and aquatic plants, in the reservoir also found other microorganisms which is phytoplankton that are mostly a member of the division Chlorophyta (green algae). Chlorophyta are the largest group of vegetation algae, this algae has a green clear color as in higher plants because it contains the pigment chlorophyll a and chlorophyll b more dominant. Species of the division Chlorophyta found in several posts in the Sumber Air Jaya reservoir are Spirogyra sp., Ulothrix sp., and Closterium sp. with different characteristics of each species.